汉语附着词的中介语分析 = Interlanguage Analysis of Clitics in Chinese - Zhi, Chen (Sinología hispánica. China Studies Review, 2015)
本文通过中介语分析，试图发现西班牙语 母语者在习得汉语附着词时容易出现的偏误类 型，并提出相应的学习策略。汉语作为典型的 孤立语，句法关系及语法内涵的表达大多通过 附着词的使用来实现，因此附着词的学习对于 汉语学习者而言至关重要。西班牙语母语者由 于受其母语正迁移影响，在“体”附着词（着、 了、过）使用方面偏误较少，而在结构附着词 （的、地、得）以及语态附着词（啊、呢、吧等） 的使用上偏误较多。研究发现，发生偏误最多 的附着词是“的、了、啊、呢”。同时，通过 对学习习惯的调查发现，课堂外的沉浸式学习 相对于课堂内而言，更有助于汉语学习。 Through the analysis of interlanguage, this article tries to detect the most frequent errors that Spanish speakers often make when learning the clitics of the Chinese language. The learning of the clitics is fundamental for mastering Chinese, a typical example of the isolating languages. The syntactic relations and grammatical contents of the Chinese language highly depend on the use of the clitics. Because of the positive transference from their mother tongue, Spanish speakers more or less learn the aspectual clitics well. But when it comes to the structural and modal clitics, the result is not quite satisfactory. The most problematic clitics, according to the statistics from this article, are “de, le, a, ne”. An investigation of the study habits is also conducted. With this, we intend to emphasize the social integration and extracurricular efforts, which sometimes even weigh more than the class hours, are the determinant factors for learning a foreign language well.